Aviation Security After Four Decades, It's Time for a Fundamental Review - Jenkins, Brian Michael (RAND Corporation, 2012)
While security budgets shrink, passenger loads grow, and hostility towards security procedures increases, terrorist groups such as al Qaeda remain obsessed with attacking airplanes. In the face of these challenges and real, innovative threats, the author proposes a mechanism for conducting an independent re-examination of the strategy behind current aviation security policies and procedures-before disaster strikes.